The Role Of The State In The Acceleration Of Economic Development In The Sambas Border Area West Kalimantan - Al Qadrie, Syarif Redha Fachmi; Usmulyadi, Syarif; Elyta, Elyta (Cita konsultindo, 2023)
Economic development, especially in border areas, continues to be a concern for the central and regional governments. The gap in economic growth in the border areas occurs in Indonesia's outermost regions, one of which is in Sambas Regency, West Kalimantan, which directly borders Sarawak, Malaysia. The real form of the government. President Joko Widodo issued Presidential Instruction Number 1 of 2021 concerning the Acceleration of Economic Development in Border Areas, one of which is Sambas Regency. As for the Presidential Instruction, specifically for the Aruk border area, 21 work programs involve Ministries, Institutions, and Regional Governments. This research uses a qualitative approach, this study sees that economic development in the border area is carried out by collaboration between the Central Government and the Regional Government to accelerate economic development in the Sambas border area, West Kalimantan.